Potensi Peran Ekstrak Daun Castanopsis costata pada Sepsis: Tinjauan Sistematis terhadap Bukti Tidak Langsung dan Wawasan Mekanistik - Arna Fransisca Millyanti Purba; Gusbakti Rusip; Maya Sari Mutia; Yolanda Eliza Putri Lubis (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2026)
Sepsis is a life-threatening systemic inflammatory condition characterized by dysregulated immune responses, excessive cytokine release, oxidative stress, and progressive multi-organ dysfunction. Natural products with anti-inflammatory and antioxidant properties are increasingly investigated as adjunctive therapeutic candidates. Castanopsis costata, a Southeast Asian medicinal plant, has shown pharmacological potential in experimental studies, but its role in sepsis has not been systematically evaluated. This review assessed available evidence on the effects of C. costata leaf extract on sepsis-related outcomes in rat models. A literature search was conducted in Scopus and Google Scholar. A total of 388 records were identified, including 132 from Scopus and 256 from Google Scholar. After removing 122 duplicates, 266 records were screened against predefined eligibility criteria for animal model, sepsis induction, intervention, control, and reported outcomes. Five studies were included in the qualitative synthesis. No study directly evaluated C. costata leaf extract in experimental sepsis. However, studies using chemical organ injury models showed that C. costata leaf extract at 100–400 mg/kg significantly reduced TNF-α and IFN-γ levels, enhanced hepatic antioxidant enzyme activity, and protected liver and kidney tissues from paracetamol- and gentamicin-induced injury. Leaf fractions also demonstrated anti-inflammatory activity comparable to diclofenac sodium, strong antioxidant capacity, and no toxicity up to 5000 mg/kg/day. Although direct evidence of sepsis is unavailable, the anti-inflammatory and antioxidant effects of C. costata suggest potential relevance to sepsis pathophysiology. Further in vivo studies using established sepsis models are required.